1975
DOI: 10.1111/j.1399-0039.1975.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

LD Antigens Associated withHL‐A8and Myasthenia Gravid1

Abstract: The finding that the SD antigen HL-A8 is associated with myasthenia gravis has raised the question as to whether or not there is also an association between some specific LD antigen and myasthenia gravis a n d o r HL-A8.MLC technique was used to study LD antigens in 33 myasthenic patients. The cells of a myasthenic patient who was homozygous for both HL-A and LD products were used in MLC tests as stimulators with HL-A8 bearing cells from 24 myasthenics, their 17 relatives and 16 controls and to non-HL-A8 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…We found that in MG the association with HL-A8 was markedly higher than with LD-8a. Kaakinen et al (1975) also found that the frequency of LD-8a was slightly higher in MG patients than in normals, they found LD-8a in 45% of 33 patients. Thus, we believe that different genes are responsible for the association with HL-A8 of diseases like myasthenia gravis on the one hand, and Addison's disease on the other, in spite of the attractive idea of special genes for autoimmune reactivity.…”
Section: Discussionmentioning
confidence: 87%
“…We found that in MG the association with HL-A8 was markedly higher than with LD-8a. Kaakinen et al (1975) also found that the frequency of LD-8a was slightly higher in MG patients than in normals, they found LD-8a in 45% of 33 patients. Thus, we believe that different genes are responsible for the association with HL-A8 of diseases like myasthenia gravis on the one hand, and Addison's disease on the other, in spite of the attractive idea of special genes for autoimmune reactivity.…”
Section: Discussionmentioning
confidence: 87%
“…The MHC region is reported to be associated with MG (17,141,142). Early-onset MG and patients exhibiting thymic hyperplasia are most strongly associated with the HLA-B8, DR3 haplotype, and late-onset MG is associated with B7 and DR2 alleles (143,144).…”
Section: Igad and Myasthenia Gravismentioning
confidence: 99%
“…Fritze et al (1974) noticed thymic hyperplasia in HLA-BE positive MG patients. Kaakinen et al (1975) observed that HLA-Dw3 was strongly linked to HLA-BE, but only a little more (not significantly) in MG patients than in control subjects. The association between HLA-BE and MG was stronger than the association between Dw3 and MG. HLA-Dw3 had no independent correlation with any of the clinical parameters of MG. Tney concluded that they did not find a specifically MG-associated HLA-D allele.…”
mentioning
confidence: 79%